Synthesis and Antibacterial Evaluation of Cephalosporin Isosteres. Issue 7 (26th March 2019) - Cesta, Drew J.; Somersan Karakaya, Selin; Saito, Kohta; Javidnia, Prisca E.; Roberts, Julia; Ling, Yan; Gold, Ben S.; Lopez Quezada, Landys; Zhang, David; Abramyan, Tigran M.; Kireev, Dmitri B.; Aubé, Jeffrey; et al.
Abstract: As part of a program to explore the chemistry of β‐lactams and their derivatives, we prepared a focused set of benzazetidine, indoline, and indole heterocycles, as well as flexible unconstrained variations of the four‐membered heterocyclic compounds. These analogues mimic the three‐dimensional shape of cephalosporins but are not prone to covalent binding via ring opening. Although these analogues were inactive against the ESKAPE pathogens and Mtb, they represent unique and underexplored chemotypes for future biological screening. Abstract : A focused library of analogues was designed to mimic the three‐dimensional shape of cephalosporins but lack the electrophilic β‐lactam ring. Based on modelling, we targeted benzazetidine, indoline, and indole scaffolds, as well as flexible unconstrained variations of the four‐membered heterocyclic compounds. The compounds were prepared by a route featuring C−H functionalization and screened for antibacterial activity.